Adjunctive Statin Therapy on Cholesterol and Clinical Symptoms in Schizophrenia Treated with Risperidone - Irma Santy; Andi Ummulkhair Pawallangi Irawan; Erlyn Limoa; Fanny Wijaya; Ilma Khaerina Amaliyah Bakhtiar; Muhammad Alim Jaya (UMI Medical Journal, 2025)
Background: Schizophrenia is associated with the metabolic side effects of atypical antipsychotics, such as hypercholesterolemia. Objective: To evaluate the effect of adjuvant statin therapy on total cholesterol levels and clinical symptoms in patients with schizophrenia treated with risperidone. Methods: This randomized clinical trial was conducted on 36 patients with schizophrenia at RSKD Dadi, South Sulawesi. The subjects were randomized into risperidone-only and risperidone plus statin groups. Results: Statin adjuvant therapy reduced total cholesterol levels and improved clinical symptoms (PANSS scores) compared to the control group. Conclusion: Adjuvant statin therapy is potentially beneficial in reducing cholesterol levels and improving clinical outcomes in patients with schizophrenia receiving risperidone.